The Quality of Cervical Cancer Brachytherapy Implantation and the Impact on Local Recurrence and Disease-Free Survival in Radiation Therapy Oncology Group Prospective Trials 0116 and 0128. Issue 1 (1st January 2012) - Viswanathan, Akila N.; Moughan, Jennifer; Small, William; Levenback, Charles; Iyer, Revathy; Hymes, Sharon; Dicker, Adam P.; Miller, Brigitte; Erickson, Beth; Gaffney, David K.
Abstract : Purpose: The objective of the study was to determine the impact of brachytherapy implant quality on outcome among cervical cancer patients treated on Radiation Therapy Oncology Group prospective trials 0116 and 0128. Methods: All enrolled patients received concurrent chemoradiation followed by brachytherapy. Individual brachytherapy parameters, including the symmetry of ovoids in relation to the tandem, displacement of ovoids in relation to the cervical os, tandem bisecting the ovoids, tandem in the midpelvis, and appropriateness of packing, were scored for each implant. Multivariate Cox proportional hazards models were constructed for each parameter for local recurrence (LR), regional recurrence, distant recurrence, disease-free survival (DFS), and overall survival. Results: Records for 103 patients were analyzed. The median follow-up time was 24.5 months. Patients with unacceptable symmetry of ovoids to the tandem had a significantly higher risk of LR than patients in the acceptable group (hazard ratio [HR], 2.67; 95% confidence interval [CI], 1.11–6.45; P = 0.03). Patients with displacement of ovoids in relation to the cervical os had a significantly increased risk of LR (HR, 2.50; 95% CI, 1.05–5.93; P = 0.04) and a lower DFS rate (HR, 2.28; 95% CI, 1.18–4.41; P = 0.01). Inappropriate placement of packing resulted in a lower DFS rate (HR, 2.06; 95% CI, 1.08–3.92; P = 0.03). Conclusions: Assessment of the quality of a brachytherapy implant is imperative, as proper placement has an impact on patient DFS. If feasible, inappropriate placements should be corrected before treatment initiation. Brachytherapy applicators for cervical cancer should preferably be placed and assessed by experienced practitioners.